Coupled reactors analysis: New needs and advances using Monte Carlo methodology. (December 2016) - Aufiero, M.; Palmiotti, G.; Salvatores, M.; Sen, S.
Highlights: Extension of the Serpent MC code to compute Avery's coupled reactors coefficients. Coupling coefficients and coupled effective neutron prompt lifetimes via Monte Carlo. New Generalized Perturbation Theory capabilities to obtain coefficient sensitivities. Code-to-code comparison against ERANOS for the Avery's coefficient calculation. Verification of the Serpent sensitivity calculations against direct perturbations. Abstract: Coupled reactors and the coupling features of large or heterogeneous core reactors can be investigated with the Avery's theory; however, the complex geometries that are often encountered in association with coupled reactors, require a detailed geometry description that can be easily provided by modern Monte Carlo (MC) codes. The results presented in this paper show that the MC code SERPENT has been successfully modified in order to compute the needed quantities like coupling coefficients. Moreover, the capability for calculating sensitivities to the quantities of interest for coupling reactors has been developed and implemented in SERPENT.